The developmental and structural uniqueness of the embryo of the extremophile viviparous nematode, Tokorhabditis tufae - Yamashita, Tatsuya; Ekino, Taisuke; Kanzaki, Natsumi; Shinya, Ryoji (Frontiers in Physiology, 2023)
Viviparity, a reproductive form that supplies nutrients to the embryo during gestation, has repeatedly and independently occurred in multiple lineages of animals. During the convergent evolution of viviparity, various modifications of development, structure, and physiology emerged. A new species of nematode, Tokorhabditis tufae, was discovered in the alkaline, hypersaline, and arsenic-rich environment of Mono lake. Its reproductive form is viviparity because it is obligately live-bearing and the embryo increases in size during development. However, the magnitude of the increase in size and nutrient provisioning are unclear. We measured egg and embryo sizes at three developmental stages in T. tufae. Eggs and embryos of T. tufae at the threefold stage were respectively 2.6- and 3.6-fold larger than at the single-cell stage. We then obtained T. tufae embryos at the single-cell, lima bean, and threefold developmental stages and investigated the egg hatching frequency at three different concentrations of egg salt buffer. Removal of embryos from the uterus halted embryonic development at the single-cell and lima bean stages in T. tufae irrespective of the solution used for incubation, indicating the provision of nutrients within the uterus. Ultrastructural and permeability evaluation showed that the permeability barrier did not form during embryonic development, resulting in increased molecular permeability. This high permeability caused by the absence of the permeability barrier likely enables supply of nutrients from the mother. The structural and physiological modifications in T. tufae are like those in other viviparous animals. We conclude that T. tufae is a viviparous rather than an ovoviviparous nematode. T. tufae will facilitate investigation of the evolution of viviparity in animals.